Клінічні ознаки хронічних вірусних гепатитів та особливості метаболізму ліпідів у них - Комариця, О.Й. (Медична гідрологія та реабілітація, 2009)
Показано, что среди пациентов с ХВГ, особенно при виремии, чаще наблюдается гипоХС. В работе показано, что частота гипоТГ при ХВГ существенно больше, чем гиперТГ Поэтому при выявлении сонографических признаков жирового гепатоза у пациентов необходимо определять уровень ТГ. Низкое их содержание указывает на необходимость поиска маркеров ХВГ Прогностически неблагоприятными для течения ХВГ являются также низкие ХС-ЛПНП и ЛПНП, увеличение коэффициента ХС-ЛПВП/ЛПВП Patients with HBV and viremia present with hypo-Ch, low levels of LDL-Ch and LDL. Hyper-Ch, inactive apoB-P and viremia were not revealed in patients with HCV. Incidence of hypo-TG in chronic viral hepatitis were significantly more, than hyper-TG. Direct correlation was established between triglycerides level and cytolysis parameters: cytolysis increases in high level of TG, decreases in less TGlevel. The following criteria are prognostically unfavorable for chronic viral hepatitis; hypo-Ch, low levels of LDL-Ch and LDL, increase of HDL-Ch/HDL coefficient.